A TEACHER’S PERCEPTION OF INTRALINGUAL INTERFERENCE IN EFL SPEAKING: A NARRATIVE INQUIRY FROM A REMOTE ISLAND SCHOOL IN MADURA, INDONESIA - ach fauzi (Jurnal Citra Multidisiplin, 2026)
Intralingual interference, which refers to errors originating from the target language system itself rather than the learners’ first language, remains a persistent challenge in English as a Foreign Language (EFL) learning. However, studies examining how teachers in remote and resource-limited contexts perceive this phenomenon are still limited. This study aims to investigate an experienced EFL teacher’s perception of intralingual interference in students’ speaking performance at a public secondary school in Gili Genting Island, Madura, Indonesia. The study employed a narrative inquiry design. Data were collected through semi-structured interviews with a female English teacher (T1), a native speaker of Madurese with five years of teaching experience at the school. The data were analyzed using thematic analysis. The findings reveal that T1 identified four dominant forms of intralingual interference in students’ English speech, namely grammatical overgeneralization, phonological substitution, lexical confusion, and unsystematic code-switching. According to the teacher, these patterns are linked to students’ limited mastery of English forms and are influenced by sociocultural factors, particularly Madurese cultural identity, including social hierarchy norms, politeness, and cultural pride. T1 also perceived that these factors contribute to communication anxiety and the tendency to use indirect speech strategies in English communication. To address these challenges, the teacher highlighted culturally responsive pedagogy, targeted phonological practice, and guided translanguaging as useful classroom approaches. The study emphasizes the importance of teachers’ perspectives in understanding EFL learning challenges in geographically marginalized and culturally distinctive contexts, and highlights the need for culturally responsive teacher professional development.